Problem-based learning methods in economics subjects in Indonesian educational institutions a literature review - Devaki Kanaga Retnama (Tanjong Malim, 2023)
Problem-based learning methods in economics subjects in Indonesian educational institutions a literature review by Devaki Kanaga Retnama